2016
DOI: 10.1007/s10508-016-0804-5
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexual Function Index Short Version: A MsFLASH Item Response Analysis

Abstract: The Female Sexual Function Index (FSFI) is a psychometrically sound and popular 19-item self-report measure, but its length may preclude its use in studies with multiple outcome measures, especially when sexual function is not a primary endpoint. Only one attempt has been made to create a shorter scale, resulting in the Italian FSFI-6, later translated into Spanish and Korean without further psychometric analysis. Our study evaluated whether a subset of items on the 19-item English-language FSFI would perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 42 publications
2
29
0
1
Order By: Relevance
“…As previously established in the literature, 13 women with scores less than or equal to 26.55 were considered to have some sexual dysfunction. 5,8,[10][11][12]14…”
Section: Data Collection Variables and Analysismentioning
confidence: 99%
“…As previously established in the literature, 13 women with scores less than or equal to 26.55 were considered to have some sexual dysfunction. 5,8,[10][11][12]14…”
Section: Data Collection Variables and Analysismentioning
confidence: 99%
“…Female sexual dysfunction has been introduced as disorders of sexual functioning, desire, and pain, which is followed by adverse consequences such as negative psychological outcomes [17]. Sexual function is a major element of women's quality of life, which affects several dimensions of peri-and post-menopausal characteristics [18]. Previous studies have shown that on average, 64% of women suffer from desire difficulty, 35% of orgasm difficulty, 31% have complications with arousal conditions, and 26% with sexual pain [19].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of instruments have been developed to measure female sexual function. Among these instruments, the 19-item Female Sexual Function Index (FSFI-19) is one of the main instruments for assessing female sexual function [18]. The FSFI-19 is a self-reported instrument, consisting of 6 separate domains of female sexual function, namely desire, arousal, lubrication, orgasm, satisfaction, and pain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations